2010
DOI: 10.1017/s1471068410000207
|View full text |Cite
|
Sign up to set email alerts
|

CHR(PRISM)-based probabilistic logic learning

Abstract: PRISM is an extension of Prolog with probabilistic predicates and built-in support for expectation-maximization learning. Constraint Handling Rules (CHR) is a high-level programming language based on multi-headed multiset rewrite rules.In this paper, we introduce a new probabilistic logic formalism, called CHRiSM, based on a combination of CHR and PRISM. It can be used for high-level rapid prototyping of complex statistical models by means of "chance rules". The underlying PRISM system can then be used for sev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Our proposal is inspired by this potential-based model of probabilistic argumentation, but for abstract argumentation combined with energy-based undirected graphical models, and in particular with the graphical model of BMs. Sneyers et al (2013) tackled a similar setting of Riveret et al (2007) (but without the concern of reflecting the structure of dialogues) by defining a probabilistic argumentation logic and implementing it with the language CHRiSM (Sneyers, Meert, Vennekens, Kameya, and Sato, 2010), a rule-based probabilistic logic programming language based on constraint handling rules (CHR) (Fruhwirth, 2009) associated with a high-level probabilistic programming language called PRISM (Sato, 2008). This language must not be confused with the system PRISM for probabilistic model checking developed by Hinton et al (2006).…”
Section: Motivations and Applicationsmentioning
confidence: 99%
“…Our proposal is inspired by this potential-based model of probabilistic argumentation, but for abstract argumentation combined with energy-based undirected graphical models, and in particular with the graphical model of BMs. Sneyers et al (2013) tackled a similar setting of Riveret et al (2007) (but without the concern of reflecting the structure of dialogues) by defining a probabilistic argumentation logic and implementing it with the language CHRiSM (Sneyers, Meert, Vennekens, Kameya, and Sato, 2010), a rule-based probabilistic logic programming language based on constraint handling rules (CHR) (Fruhwirth, 2009) associated with a high-level probabilistic programming language called PRISM (Sato, 2008). This language must not be confused with the system PRISM for probabilistic model checking developed by Hinton et al (2006).…”
Section: Motivations and Applicationsmentioning
confidence: 99%
“…The system CHRat [76] implements a modular version of CHR that allows for reusing built-in constraints, defined in a constraint system, as a constraint solver in another CHR program (http: //contraintes.inria.fr/˜tmartine/chrat/). CHRiSM [198] (http: //people.cs.kuleuven.be/˜jon.sneyers/chrism/) integrates CHR and PRISM (PRogramming In Statistical Modeling) [190], a probabilistic extension of Prolog for symbolic-statistical modeling.…”
Section: Interpreters For Ccp Calculimentioning
confidence: 99%
“…Basically, in the distribution semantics all facts are assumed to be mutually independent [Hommersom and Lucas 2011]. Similar assumptions are made in certain other logics such as Independent Choice Logic [Poole 2008] and PRISM [Sato 1995;Sneyers et al 2010]. Subrahmanian [1992, 1993] propose probabilistic logic programs where the independence assumption is not required, but this is computationally expensive though recent approaches [Khuller et al 2007] based on sampling have been shown to scale very well to the case of 100K atoms.…”
Section: Related Work In Logic Programmingmentioning
confidence: 99%
“…In many logics that incorporate independence assumptions including [Poole 2008;Raedt et al 2007;Sneyers et al 2010], the probability of diffusion from neighbors of a vertex to a vertex are computed via the independence assumption. In the simplest sense, consider a vertex v and two vertices a, b such that (a, v), (b, v) are edges in the graph and suppose there are no other edges of the form (−, v).…”
Section: Related Work In Logic Programmingmentioning
confidence: 99%
See 1 more Smart Citation